Some issues concerning the protection of trade secret and the completion of trade secret protection legislation in Vietnam - Nguyen, Thi Que Anh (Đại học Quốc gia Hà Nội, 2017)
The paper presents studies on some theoretical issues of protection of business secrets and the implementation of the law on protection of business secrets of Vietnam. Based on scientific analysis, the author summarizes the legal system of protection of business secrets in the world, which describes the characteristics of business secrets and criteria for the protection of business secrets as the subject matter of intellectual property rights and at the same time provide solutions to the implementation of the law and improve the effectiveness of protection of business secrets in Vietnam.